INTERCULTURAL COMMUNICATION IN FOREIGN LANGUAGE TEACHING AND ITS METHODOLOGICAL FOUNDATIONS - Erkinov Ahrorbek (Next Scientists Conferences, 2025)
This article is devoted to analyzing the methodological foundations of intercultural communication in foreign language teaching. In the context of globalization processes and intensifying intercultural relations, the process of learning a foreign language requires not only the development of linguistic competencies, but also the formation of intercultural communication abilities. Modern methodological approaches, pedagogical strategies and practical methods for developing intercultural communication competencies are analyzed. According to research results, the intercultural approach in foreign language teaching significantly enhances not only students' language skills, but also cultural understanding and empathy abilities. The article examines the theoretical foundations of intercultural competence formation, practical strategies and assessment mechanisms.